Awareness on Breast Feeding among Readymade Garments (RMG) Working Women in Dhaka city (Bangladesh Journal of Medicine, 2013)
Back ground: Breast-feeding is the unique source of nutrition that plays an important role in the growth, development and survival of infants. There are lots of readymade garments working (RMG) women in Dhaka city who have poor facilities for their childs breast feeding which is not only a National issue but also an International issue. Objective: To identify the awareness on breast feeding among RMG working women in Dhaka city. Methods: Descriptive Cross Sectional study was conducted among RMG Women in Dhaka City, aged 1549 years. The study conducted in Readymade Garments factory at Mirpur Police station area in Dhaka city during the period of January 2009 to June 2009. The sample size for the cross sectional study was calculated by using Z test and it was 625. Result: About 94.5% of the mothers attempted breastfeeding. At 1 month, 71.6% were still breastfeeding, 49.6% continued to do so at 2 months, and 29.8% persisted till 4 months. By 6 months, the breastfeeding prevalence rate fell to 21.1%. The median duration of breastfeeding was 7.0 weeks and the mean duration was 12.7 weeks. The median duration of breastfeeding was shorter than the mean duration as the proportion of mothers who continued breastfeeding was smaller than that of mothers who stopped breastfeeding; and among those who persisted, their average duration were longer. Among the mothers who attempted breastfeeding, the shortest duration was 0.5 weeks, while 21.1% were still doing so at the end of 6 months. Conclusions: Many women would also find it useful to have more flexible working hours. In some work settings, giving women with young infants extra flexibility in work hours might be a low-cost and effective intervention DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13613 Bangladesh J Medicine 2010; 21: 65-70